CONCEPTUAL AND CATEGORIAL ANALYSIS OF INTEGRATION OF SCIENTIFIC RESEARCH AND EDUCATIONAL ACTIVITY OF FUTURE TEACHERS OF MATHEMATICS - Linnik, Elena; Ovchinnikova, Marina; Shilova, Lyubov (Revista Inclusiones, 2020)
The urgency of the problem is caused by the need to resolve the contradiction between the requirements for improving the quality of professional and pedagogical training for future mathematics teachers by forming and integrating their educational and research activities at a high level as well as by the insufficient interpenetration and integration of these activities in the educational process of a higher educational institution. The purpose of the article is to raise the problem of integrating the main activities of future mathematics teachers in the course of their personality-centered training, refining and concretizing the definitions of such concepts as "the educational activity of the future mathematics teacher", "the scientific research activity of the future mathematics teacher", "the integration of educational and scientific research activity of the future teacher of mathematics ".